SELFIDENIFICATION AND THE PROBLEM OF A PERSON FORMATION IN THE PHILOSOPHY OF PSYCHOANALYSIS - Новак, Т. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article aims at the research of correlation between selfidenification and the problem of a person formation in the philosophy of psychoanalysis.